ANALISIS ALOKASI ANGGARAN PEMELIHARAAN KENDARAAN DINAS DI KABUPATEN ENDE TAHUN 2008 - 2010 - , Mayela Wuga ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study with a title of Analysis of The Allocation of Budget for Official Vehicle Maintenance in Ende Regency during 2008-2010 aims at examine the effect of the number of office vehicle asset value on the number of the allocation of budget for office vehicle maintenance, at finding out the rate of efficiency and the targeted allocation of budget for office vehicle maintenance of the local Government Working Unit and at finding out whether or not there is difference in the average allocation of budget for office vehicle maintenance between the Local Government Working Units producing Local Income and the Local Government Working Units not producing Local Income in Ende Regency. The examination was done by using the panel data regression analysis, Data Envelopment Analysis (DEA), and Independent Samples t-test. Result of the panel data regression test indicates that the number of office vehicle asset value did not affect the number of budget for office vehicle maintenance. The result was affected by change in the number of budget for office vehicle maintenance, which decreased in 2009 and increased in 2010. The underlying cause of the decrease was the massive budget for office vehicle maintenance in two Local Government Units in 2008 and the policy the Chairman of Regency on the ordering of the use of office vehicle in 2009. Result of the DEA indicates that the allocation of budget for office vehicle maintenance in the Local Government Working Units were not efficient in average. The difference in the average allocation of budget for office vehicle maintenance between the Local Government Units producing Local Income and the Local Government Working Units nor producing Local Income taken place in 2009.